Distinct Expression Patterns of Apoptosis and Autophagy-Associated Proteins and Genes during Postnatal Development of Spiral Ganglion Neurons in Rat. (17th October 2020) - Hou, Shule; Chen, Penghui; Chen, Jiarui; Chen, Junmin; Sun, Lianhua; Chen, Jianyong; He, Baihui; Li, Yue; Qin, Huan; Hong, Yuren; Li, Shuna; He, Jingchun; et al.
Abstract : Autophagy and apoptosis have a complex interplay in the early embryo development. The development of spiral ganglion neurons (SGNs) in addition to Corti's organ in the mammalian cochlea remains crucial in the first two-week postnatal period. To investigate the roles of apoptosis and autophagy in the development of SGNs, light microscopy was used to observe the morphological changes of SGNs. The number of SGNs was decreased from P1 to P7 and plateaued from P10 to P14. Immunohistochemistry results revealed positive expression of cleaved-caspase3, bcl-2, microtubule-associated protein light chain 3-II (LC3-II), Beclin1, and sequestosome 1 (SQSTM1/P62) in SGNs. The apoptotic bodies and autophagosomes and autolysosomes were also identified by transmission electron microscopy at P1 and P7. Real-time PCR and western blotting results revealed that the apoptotic activity peaked at P7 and the autophagy activity was gradually upregulated along with the development. Taken together, our results for the first time showed that autophagy and apoptosis in SGNs play distinct roles during specific developmental phases in a time-dependent manner.